A bibliometric study of literature in records management journal - Azman, Kamarul Azwan; Yunus, Mohd Nizam; Kamarudin, Hanis Diyana (2012)
A bibliometric analysis of 235 articles published in Records Management Journal from 1994-2009 was carried out. The range of article published per volume is between 9 and 17. Average number of citation per article is 26.4 while 33.2% of the articles are research oriented. Most paper (80%) is single authored which consist of 187 authors out of a total of 235 authors. Elizabeth Shepherd, the most prolific author contributed 7 papers while Julie Mcleod and Zawiyah M. Yusoff contributed 6 papers which ranked in second place. 174 (59.2%) of the authors are geographically affiliated to United Kingdom. The most productive institution/organization is University of Northumbria, United Kingdom with 24 out of 187 authors. Subject analysis indicates that "Systems Design and Implementation" outnumbered other subjects with 15.8% (37) out of total of 235 articles. Most of the cited publications (97.7%) are in English Languages. Journal articles outnumbered other types of cited materials with 28.1% (810) from the total of 2,883 and Records Management Journal itself is the most cited journal with 127 (15.7%) frequencies.